2022
DOI: 10.3390/bioengineering9030107
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Magnesium Biomaterials—Road to the Clinic

Abstract: In recent decades, we have witnessed radical changes in the use of permanent biomaterials. The intrinsic ability of magnesium (Mg) and its alloys to degrade without releasing toxic degradation products has led to a vast range of applications in the biomedical field, including cardiovascular stents, musculoskeletal, and orthopedic applications. With the use of biodegradable Mg biomaterials, patients would not suffer second surgery and surgical pain anymore. Be that as it may, the main drawbacks of these biomate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 196 publications
0
12
0
1
Order By: Relevance
“…These observations are corroborated by a variety of previous studies. It has been widely reported that the released Mg ions during material degradation regulated gene and protein expression associated with MSCs growth and differentiation, and its effects were highly dose-dependent [ 46 , 47 ]. A variety of works exposing the cells to different ranges of Mg ion concentrations, prepared from the dissolution of Mg salts or present in extracts from Mg-based materials, has been reported attempting to estimate an optimized value.…”
Section: Resultsmentioning
confidence: 99%
“…These observations are corroborated by a variety of previous studies. It has been widely reported that the released Mg ions during material degradation regulated gene and protein expression associated with MSCs growth and differentiation, and its effects were highly dose-dependent [ 46 , 47 ]. A variety of works exposing the cells to different ranges of Mg ion concentrations, prepared from the dissolution of Mg salts or present in extracts from Mg-based materials, has been reported attempting to estimate an optimized value.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies reported that there were no health risks following Mg implantation in rats with chronic renal failure [ 25 ]. The results of an in vivo study indicated that Mg absorption, after implantation of Mg alloy rods, at the degradation rate of 2.32 mm/yr did not lead to dysfunction of the heart, liver, kidney, and spleen of the rabbits [ 26 ]. Moreover, Mg alloy rods inserted in the femoral bone of the New Zealand rabbits did not cause changes in the Mg serum levels, kidney and liver function, and histological structure of the vital organs, like the heart and spleen [ 27 ].…”
Section: Biological Properties Of Mg-based Materialsmentioning
confidence: 99%
“…Out of these three things (scaffold, cells, and growth factors), the focus of this review is on the scaffold. A bone scaffold that mimics the properties of natural bone is crucial which includes sufficient porosity, biocompatibility, osteoinductive activity, and antibacterial property as well as optimal mechanical properties and degradability. ,,, Alloys and biodegradable metals have been widely used as scaffolds for bone repair, as their properties harbor great mechanical stiffness, meeting the high demands of mechanical support in human. However, the degradation rates of these biomaterials are fast and cannot match with the natural bone healing rate, resulting in limitations for biomedical applications which need structural optimization of scaffolds to delay their degradation rates. Metallic ions could regulate cell behavior, ,, and it has been reported that these ions can play important roles in the bone regeneration itself. Therefore, integrating bone scaffolds with metal ions is a promising trend in bone tissue engineering. Zinc, magnesium, and iron ions are available metal ions, belonging to the element of natural bone.…”
Section: Introductionmentioning
confidence: 99%